THE IMPACTS OF INVESTMENT IN THE FORESTRY SECTOR ON THE INDONESIAN ECONOMY - Sahara Sahara; Wildan Nur Arrasyiid Sane Pratinda; Deden Djaenudin (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2022)
Indonesia has abundant forest resources, reaching 120 million hectares of forest area. However, the forestry sector's contribution to the national economy continues to decline. The low performance of the forestry sector cannot be separated from the limited availability of round-wood materials for its processing industries and insufficient development of the multi-businesses activities among the forestry companies. Therefore, increasing the forestry sector's productivity is necessary through raising investment. This study investigates the impacts of investment in the forestry sector on Indonesian economic performance, including output, income, employment, and import, using the Input-Output (I-O) Model. The results show that investment in the forestry sector will increase output, income, and labour in the forestry sector and its related sectors. However, with the increase in its output, the demand for inputs, including round-wood materials, will also increase, encouraging a rise in imports. Thus, an increase in investment in the forestry sector needs to be balanced with the availability of roundwood materials and other associated inputs in Indonesia. For the follow-up research, it is important to separate the investment into upstream and downstream activities along the forestry value chain and include a regional aspect in the analysis.